(untitled) (Fiep Bulletin - online, 2024)
The sprint modality of the orienteering sport is a medium-duration event (12-15min) with peaks of intensity and consequently variations in metabolic demand. The ability to specifically recruit muscular action without reducing performance is crucial to the athlete’s final result. The training methodology used in this modality must consider anaerobic metabolism, even with less participation throughout the event, as an important factor limiting performance. Based on this observation, the present study aimed to evaluate the need to use half-distance and long-distance training forms as a basis for athletes in this sprint modality. The available literature provides important information based on medium and long-distance events, however there is an important gap regarding sprint events. Despite this, the available information contributed to demonstrating that anaerobic metabolism is an important factor determining performance. It was then concluded that the sports season training program must include aspects of anaerobic training with the objective of improving performance in sprint orienteering events, minimizing the effects of increased blood lactate due to intensity peaks and variation in running speed during the competition.